Increase of Type 2 Ryanodine Receptors in Mouse Nucleus Accumbens in the Development and Expression of Morphine-Induced Place Preference - Kazuhiro Kurokawa; Koji Mizuno; Seitaro Ohkuma (Elsevier, 2014)
Abstract.: The present study investigated the effect of ryanodine receptors (RyRs) in the development and expression of morphine-induced conditioned place preference (CPP). Type 2 RyRs (RyRs-2) in the nucleus accumbens (NAcc) significantly increased in morphine-conditioned mice, whereas type 1, 2, and 3 RyRs in the frontal cortex and ventral tegmental area showed no changes. Intracerebroventricular pretreatment with dantrolene, a RyRs antagonist, during the conditioning phase of CPP, dose-dependently inhibited morphine-induced CPP. The expression of morphine-induced CPP was abolished by dantrolene administration before the post-conditioning test. These findings suggest that RyRs-2 in the NAcc participate in the development and expression of morphine-induced CPP. Keywords:: Type 2 ryanodine receptor, morphine, conditioned place preference